1984
DOI: 10.1254/jjp.36.59
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bestatin-Sensitive Aminopeptidase, Angiotensin Converting Enzyme and Thiorphan-Sensitive "Enkephalinase" in the Potency of Enkephalins in the Guinea-Pig Ileum

Abstract: Abstract-The role of each enkephalin-hydrolyzing peptidase in the inhibitory potency of exogenously added enkephalins in the myenteric plexus-longitudinal muscle preparation of guinea-pig ileum was studied by using the relatively specific inhibitor of each enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…11 and peptidyl dipeptidase A are found to be inhibited maximally with either thiorphan or phosphoramidon and captopril at the dose of 1 or 1 and 1 fM, respectively. The dose of each inhibitor to depress the activity of the enkephalin hydrolyzing enzyme maximally in the mouse vas deferens obtained in the present study is the same as that previously obtained in the guinea-pig ileum (1).…”
Section: Chemicalssupporting
confidence: 64%
See 1 more Smart Citation
“…11 and peptidyl dipeptidase A are found to be inhibited maximally with either thiorphan or phosphoramidon and captopril at the dose of 1 or 1 and 1 fM, respectively. The dose of each inhibitor to depress the activity of the enkephalin hydrolyzing enzyme maximally in the mouse vas deferens obtained in the present study is the same as that previously obtained in the guinea-pig ileum (1).…”
Section: Chemicalssupporting
confidence: 64%
“…Additionally, it has shown that these enzymes are likely to be located close to opioid receptors (1). On the other hand, both L-tyrosyl-L-tyrosine sensitive dipeptidyl aminopeptidase and D phenylalanine-sensitive carboxypeptidase have been indicated not to be involved sig nificantly in the degradation of enkephalins in guinea pig ileum (1), although these two peptidases have been reported to be im plicated in the hydrolysis of enkephalin in the brain (2,3).…”
mentioning
confidence: 99%
“…A mixture of an aminopeptidase inhibitor, a peptidyl dipeptidase A inhibitor and an enkephalinase inhibitor has been shown to completely protect Met-enk from degradation produced by incubation with either an ileal or a striatal membrane fraction from guinea pigs (15). Also, it has been shown that the effects of Met-enk in vivo and in vitro were potentiated by the mixture of peptidase inhibitors; the loss of the righting reflex and the inhibition of the tail-flick response were produced by Met-enk ad ministered s.c. in infant rats pretreated with the mixture of three peptidase inhibitors (16), and the inhibitory effect of Met-enk on the contraction of isolated ileum (17,18) and vas deferens (17,19,20) were increased by the mix ture of peptidase inhibitors. However, the enzymatic degradation of p-end and Dyn is not fully understood, and the involvement of the Met-enk hydrolyzing enzymes in the degradation of A-end and Dyn in CNS is not clear.…”
Section: Introductionmentioning
confidence: 96%
“…The control experiment: The IC50 value of [Met5]-enkephalin was repeatedly estimated for five times in six preparations of rat vas deferens in order to examine the stabi ity of the response of the preparation to an opioid during the usual experimental period, since it has been shown that the sensitivity to an opioid of rabbit vas deferens was significantly increased with the passage of time (9), while that of guinea-pig ileum was not significantly changed during the usual experimental period (1). The IC50 values of [Met5] enkephalin estimated initially and secondarily were significantly higher than those estimated secondarily and thirdly, respectively ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…11 ("enkephalinase", EC 3.4.24.11), and captopril-sensitive peptidyl dipeptidase A (angiotensin I converting enzyme, kininase II, peptidyldipeptide hy drolase, EC 3.4.15.1), have been shown to play important roles in the inactivation of exogenously given enkephalin in two in vitro isolated preparations, guinea-pig ileum (1) and mouse vas deferens (2). Additionally, these three enzymes have been indicated to be located very close to opioid receptors (1,2). Moreover, enkephalin has been shown to be exclusively inactivated by these three peptidases, since enkephalin remains intact almost totally after it is incubated with either ileal or striatal membrane fractions of guinea pig for 60 min at 37'C in the presence of three peptidase inhibitors, amastatin, thior phan and captopril, although free tyrosine and the Tyr-Gly-Gly fragment are produced when the incubation mixture does not contain the peptidase inhibitor (3).…”
Section: Deferensmentioning
confidence: 99%